(untitled) (Fiep Bulletin - online, 2013)
The area of the human development, specifically the infantile development, intends to understand the occurred transformations in this period and, to verify, by evaluations, the real and waited state for determined phase of the development. In this direction, the objective of the study was to identify the nutritional state of children of both sexes, with ages between 7 and 10 years regularly registered in a public school in the city of Boa Vista /RR and classifies them in accordance to the considered criteria of health. The study was characterized as descriptive-exploratory, the sample was composed for 311 scholars, being 154 boys with average age of 8,3±1,1 years and 157 girls with average age of 8,4±1,1 years. The used instruments were a digital scale (corporal mass), an estadiometer (height) and the registration form of the children in the school (age). The nutritional state was related by the Index of Corporal Mass (IMC) using the criteria of Conde & Monteiro (2006). For analysis of the data it was used descriptive statistics (average, shunting line standard and distribution in frequencies and percentages). For comparison between the sexes test “t” of student was used for independent samples. In relation to the averages of the IMC an increment in the values with passing of the age in both sexes can be observed, but in the female with 10 years of age. When carried through test “t” in the general sample significant differences (p 0,05>) between the sexes had not been found. The biggest concentration of individuals was identified in the classification of eutrophic with 86,4% for boys and 82.2% for the girls. In a general way it can be concluded that the nutritional state of the evaluated citizens is presented inside of normality, without representative values in the extreme degrees of the proposals classifications for this study.